2012
DOI: 10.3109/15412555.2012.654923
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Pulmonary-Radiology Workshop for Visual Evaluation of COPD: Study Design, Chest CT Findings and Concordance with Quantitative Evaluation

Abstract: The purposes of this study were: to describe chest CT findings in normal non-smoking controls and cigarette smokers with and without COPD; to compare the prevalence of CT abnormalities with severity of COPD; and to evaluate concordance between visual and quantitative chest CT (QCT) scoring Methods Volumetric inspiratory and expiratory CT scans of 294 subjects, including normal non-smokers, smokers without COPD, and smokers with GOLD Stage I-IV COPD, were scored at a multi-reader workshop using a standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 24 publications
11
113
0
1
Order By: Relevance
“…We assessed emphysema quantitatively, which has much greater precision than radiologist assessment but for which a standard threshold of normality is currently lacking. 58,59 Therefore, we used an arbitrary but reasonable threshold of the median value of percent emphysema. Sensitivity anal yses showed that results were similar using a 25th percentile threshold and using a 2 950 HU definition (median or 25th percentile) to defi ne percent emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed emphysema quantitatively, which has much greater precision than radiologist assessment but for which a standard threshold of normality is currently lacking. 58,59 Therefore, we used an arbitrary but reasonable threshold of the median value of percent emphysema. Sensitivity anal yses showed that results were similar using a 25th percentile threshold and using a 2 950 HU definition (median or 25th percentile) to defi ne percent emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…In the COPDGene® workshop, where 58 observers independently scored CT scans of 294 individuals, agreement on pattern and extent of emphysema was poor to moderate, and concordance between visual and quantitative assessment of the presence of emphysema was only 75%. 61 Gietema, et al, found that in those with less severe categories of emphysema, radiologists tended to visually underestimate extent of emphysema compared with quantitative measures, while in those with more severe emphysema, the radiologists tended to relatively overestimate emphysema extent. Thus, QCT and visual evaluation may provide complementary, independent assessments of severity of emphysema, particularly in those with less severe abnormality.…”
Section: Concordance Between Qct and Visual Evaluationmentioning
confidence: 99%
“…To precisely investigate the relationship between emphysema subtypes and airflow limitation, extent of emphysema subtypes should be evaluated. Although it is possible to assess emphysema subtypes visually, the visual assessment was time-consuming and suffered from inter-observer variability [7]. To overcome these problems, automated CT quantification of emphysema subtypes should be pursued, which would provide additional benefits with radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…However, visual assessment of emphysema is subjective and time-consuming, and suffers from inter-observer variability [7]. For example, kappa values for detection of centrilobular emphysema (CLE), panlobular emphysema, and paraseptal emphysema (PSE) ranged from 0.29 to 0.59 [7], and the inter-observer variability in emphysema subtypes was not acceptable. Under these circumstances, importance of automated CT quantification of emphysema has been recognized, which provides objective and reproducible evaluation of COPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation